#MeToo and modernism - Field, Robin E., 1976-; Jordan, Jerrica (Clemson University Press, 2022)
"#MeToo and Modernism opens new critical conversations about modernism and power, privilege, and patriarchy to uncover a united literary movement against sexual violence. This volume showcases how authors, whether purposely or not, challenge patriarchal viewpoints regarding sexuality, gender, and race and allowed readers different methods of interpretation for trauma narratives"-- Provided by publisher.
Keywords: Sex crimes in literature.; Literature -- History and criticism.; Misogyny in literature.; Feminism in literature.; Modernism (Literature); MeToo movement.; Literature -- Study and teaching.; Violence sexuelle dans la littérature.; Littérature -- Histoire et critique.; Misogynie dans la littérature.; Féminisme dans la littérature.; Modernisme (Littérature); Mouvement #MoiAussi.; Littérature -- Étude et enseignement.; Feminism in literature; Literature; Literature -- Study and teaching; MeToo movement; Misogyny in literature; Sex crimes in literature; Criticism, interpretation, etc.; Essays; Literary criticism; Literary criticism.; Essays.; Critiques littéraires.